2018
DOI: 10.3389/fphys.2018.00233
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic and Metabolic Assessment of Neonates With Punctate White Matter Lesions Using Phase-Contrast MRI and T2-Relaxation-Under-Spin-Tagging (TRUST) MRI

Abstract: The brain's hemodynamic and metabolism of punctate white matter lesions (PWML) is poorly understood due to a scarcity of non-invasive imaging techniques. The aim of this study was to apply new MRI techniques to quantify cerebral metabolic rate of oxygen (CMRO2), global cerebral blood flow (CBF), oxygen saturation fractions in venous blood (Yv) and oxygen extraction fraction (OEF) in neonates with PWML, for better understanding of the pathophysiology of PWML. Fifty-one newborns were recruited continuously, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(37 citation statements)
references
References 46 publications
2
33
2
Order By: Relevance
“…Our data demonstrated an 18% overestimation of neonatal blood flow in PC MRI scans acquired at 0.4 and 0.5 mm resolutions compared with that acquired at 0.3 mm resolution. Several previous studies have reported CBF measurements in neonates using PC MRI with low imaging resolutions, such as 1 mm, 0.6 mm, and 0.5 mm . Therefore, our results suggest that interpreting literature values of CBF acquired with low PC resolutions should be done with an abundance of caution regarding overestimation.…”
Section: Discussionmentioning
confidence: 56%
See 4 more Smart Citations
“…Our data demonstrated an 18% overestimation of neonatal blood flow in PC MRI scans acquired at 0.4 and 0.5 mm resolutions compared with that acquired at 0.3 mm resolution. Several previous studies have reported CBF measurements in neonates using PC MRI with low imaging resolutions, such as 1 mm, 0.6 mm, and 0.5 mm . Therefore, our results suggest that interpreting literature values of CBF acquired with low PC resolutions should be done with an abundance of caution regarding overestimation.…”
Section: Discussionmentioning
confidence: 56%
“…When combined, they provide an assessment of the brain's oxygen consumption, specifically the cerebral metabolic rate of oxygen (CMRO 2 ) . These biomarkers have significant implications in brain development and pathological conditions in neonates, such as hypoxic ischemic encephalopathy, hydrocephalus, congenital heart disease, and punctate white matter injury . Although several studies have demonstrated proof of principle of these measurements with MRI, the techniques and imaging parameters used were diverse and, more importantly, there has not been a systematic effort at sequence characterization.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations